Horticultural activities can achieve the same affect improvement effect of green exercise: A randomized field controlled trial - Tao, Meng; Lu, Li; Gao, Jingchuan; He, Xiaolong (Frontiers in Psychology, 2022)
Objectives With the deepening of non-drug intervention research on human mental health, more and more attention has been paid to the benefits of horticultural activities and green exercise on physical and psychological health. This study compared the affect improvement between horticultural activities with the same intensity and green exercise and that with or without green plants to verify the value of horticultural activities and green exercise in improving human affect and the importance of green plants. Methods A total of 160 subjects aged 18–26 years (average age 22.5 years) were recruited and randomly divided into a control group, a horticultural activity group with green plants, a horticultural activity group without green plants, and a green exercise group. Demographics, sociological variables, and daily physical activity levels were investigated. Green space at Zhejiang Normal University was selected as the test site. After finishing the preparation work, the subjects sat quietly for 8 min before the pre-test. The horticultural group completed 20 min of horticultural activities 8 min of digging [40%*HRR(heart rate reserve) + RHR(resting heart rate)] + 8 min of transplantation [(50%*HRR + RHR) + 4 min of watering (30%*HRR + RHR)]. The group returned to a calm state (no less than 20 min) for the post-test. The green exercise group completed a 20-min power bike ride. The activity intensity and activity time of the green exercise group were determined according to the activity intensity and time of the horticultural group. Dependent variables were collected, including blood pressure, positive/negative affects, heart rate variability (RMSSD, SDNN, and LF/HF), and controlled covariate environmental parameters (field temperature, humidity, and noise). Results (1) A significant difference was observed in the improvement effect except for negative affect between the green horticultural activity group and the green exercise group (F = 3.310; ɳp2 = 0.046; p = 0.037). No significant difference was observed in other affect indicators. (2) In the same pattern of with and without green plant horticultural activity group, the green plant horticultural activity group had a better effect on the improvement of affect, and the two groups had a better negative affect (F = 3.310; ɳp2 = 0.046; p = 0.037), SDNN index of heart rate variability(F = 1.035; ɳp2 = 0.015; p = 0.039), and RMSSD index (F = 2.225; ɳp2 = 0.032; p = 0.014), and no significant difference was observed in the improvement effect of other affect indicators between the two groups. Conclusions Having green horticulture can give the same intensity as green exercise and affect improvement. Findings suggest that people can choose green exercise or horticultural activities according to their preferences and physical characteristics in the two physical activities. Under the same pattern of horticultural activities, green plants are the key factor in improving the affect of horticultural activities. Choosing suitable plant types in horticultural activities is positively significant in enhancing affect.